Convergence Insufficiency Identifies Athletes at Risk of Prolonged Recovery From Sport-Related Concussion. (August 2017) - DuPrey, Kevin M.; Webner, David; Lyons, Adam; Kucuk, Crystal H.; Ellis, Jeffrey T.; Cronholm, Peter F.
Background: Sensitive and specific screening methods are needed to identify athletes at risk of prolonged recovery after sport-related concussion (SRC). Convergence insufficiency (CI) is a common finding in concussed athletes. Purpose: To assess the relationship between CI and recovery after SRC at the initial office visit. Study Design: Case-control study; Level of evidence, 3. Methods: In this retrospective cohort study, 270 athletes (147 male, 123 female), mean ± SD age 14.7 ± 2.0 years (range, 10-21 years), with the diagnosis of SRC who presented for initial office visit between January 2014 and January 2016 were evaluated for near point of convergence (NPC). The athletes were categorized into 2 groups: normal near point of convergence (NPC ≤6 cm), and convergence insufficiency (NPC >6 cm). These athletes were then followed to determine recovery time. Results: Athletes presented for initial office visit at a mean of 5.2 ± 4.2 days (range, 1-21 days) after SRC. Half of the athletes had CI after SRC (50.4%; n = 136). Athletes with CI (NPC 12.3 ± 4.7 cm) took significantly longer to recover after SRC, requiring 51.6 ± 53.9 days, compared with athletes with normal NPC (4.1 ± 1.3 cm), who required 19.2 ± 14.7 days ( P < .001). After controlling for potential confounding variables, CI significantly increased the odds of prolonged recovery (≥28 days from injury) by 12.3-fold ( P < .001; 95% confidence interval, 6.6-23.0). CI screening correctly classified 75.2% of our sample with 84.2% sensitivity and 70.0% specificity. The positive predictive value for CI and prolonged recovery was 62.5%, and the negative predictive value was 88.1%. Conclusion: CI at the initial office visit identified athletes at increased risk of prolonged recovery after SCR. Clinicians should consider measuring NPC in concussed athletes as a quick and inexpensive prognostic screening method.